The Influence of Brand Awareness and Brand Ambassadors on Vivo Cellphone Purchase Decisions for Eka Prasetya Medan Students - Dennis (Outline Journal of Management and Accounting, 2022)
This study aims to determine the effect of Brand Awareness and Brand Ambassador on Purchase Decisions for VIVO Smartphone at STIE Eka Prasetya Medan Student.The research methodology used is descriptive quantitative method. The population in this study amounted to 1.122 respondents and as the sample are 92 respondent. The results of the analysis show that the brand awareness has a positive and significant effect on the Purchase Decisions for VIVO Smartphone at STIE Eka Prasetya Medan Student on the partial test results. The results showed that Brand Ambassador is not effect and no significant on Purchase Decisions for VIVO Smartphone at STIE Eka Prasetya Medan Student based on the results of partial tests. The results showed that Brand Awareness and Brand Ambassador has a positive and significant effect on Purchase Decisions for VIVO Smartphone at STIE Eka Prasetya Medan Student based on simultaneous test results. The results of this study are supported by the value of R Square which means Brand Awareness and Brand Ambassador can explain purchasing decisions and the remaining influenced by other variables outside of this study such as Price, and Perception.